Wheat and the irritable bowel syndrome – FODMAP levels of modern and ancient species and their retention during bread making. (August 2016) - Ziegler, Jochen U.; Steiner, Deborah; Longin, C. Friedrich H.; Würschum, Tobias; Schweiggert, Ralf M.; Carle, Reinhold
Highlights: Fermentable oligo-, di- and monosaccharides, and polyols (FODMAP) were analysed. FODMAP levels ranged from 1.2 to 2.0 g/100 g DM in flours of 5 wheat species. Dough proofing times decisively determined FODMAP contents in wheat breads. FODMAP levels in wheat breads were effectively diminished by up to 90%. Wheat products for IBS patients may be obtained by specific processing methods. Abstract: Dietary intake of fermentable oligo-, di- and monosaccharides, and polyols (FODMAP) has previously been shown to aggravate the symptoms of the irritable bowel syndrome (IBS), furthermore being associated with wheat sensitivity and a bread wheat-specific intolerance. FODMAP in whole grain flours and breads made of different varieties of bread wheat, spelt, durum, emmer, and einkorn were determined by high-performance anion exchange chromatography with pulsed amperometric detection. Fructans and raffinose were the only FODMAP detected in wheat flour. Total FODMAP contents ranged from 1.24 ± 0.38 to 2.01 ± 0.42 g/100 g DM in emmer and einkorn flours, respectively. During bread making, prolonging dough proofing times (>4 hours) allowed to effectively diminish FODMAP levels of the final product by up to 90%. Therefore, the applied processing method was substantially more important than the selection of the used variety in order to obtain low-FODMAP wheat bakery products, suitable for consumption by IBS patients.